Crianças no YouTube: um estudo etnográfico sobre as infâncias e suas estratégias de relacionamento nas mídias digitais - Kuntz, Fárida Monireh Rabuske (2018)
This monograph explores the participation of children in the context of content production in digital media, and aims to comprehend how they use the space in the YouTube platform for expression, sociability and social enhancement. After reviewing the state of the art regarding the object of study and reflecting upon the propositions previously formulated, a theoretical discussion on consumption, digital media, digital culture and childhood is disclosed. In the methodological section, empirical examples of children personalities from popular YouTube channels are presented and studied through triangulation with content and speech analyses, aiming to justify the social phenomenon that concern this monograph. The most important contribution of the monograph lies in the ethnographic approach, for which we observe the interactions on the platform and approximate with some young youtubers. The obtained results indicate the relevance of investigating the still underexplored phenomenon of internet content produced by children, whose participation reveals traces of autonomy on the social action, even if they are, in most cases, advised/tutored by their parents. The YouTube platform presents itself as a tool for expanding children sociability, given that the platform may serve as an expander and strengthener of social and family bounds. The conclusions of this research indicate that there is social value on the activity of young youtubers. Their practice is absolutely related to activity (and not passivity) in relation with the media, and their meaning is in the interaction (when they like, comment, follow and search subscribers, visualizations and likes). The discussion sheds light on the complexity of the topic, which calls for continuity and deepening in future research.